The Protoplanetary Disc Around Hd 169142 Circumstellar or Circumbinary? - Perez-Marquez, S (Oxford University Press, 2022)
Stellar binaries represent a substantial fraction of stellar systems, especially among young stellar objects. Accordingly, binaries play an important role in setting the architecture of a large number of protoplanetary discs. Binaries in coplanar and polar orientations with respect to the circumbinary disc are stable configurations and could induce non-axisymmetric structures in the dust and gas distributions. In this work, we suggest that the structures shown in the central region of the protoplanetary disc HD 169142 are produced by the presence of an inner stellar binary and a circumbinary (P-type) planet. We find that a companion with a mass ratio of 0.1, semimajor axis of 9.9 au, eccentricity of 0.2, and inclination of 90°, together with a 2 MJ coplanar planet on a circular orbit at 45 au reproduce the structures at the innermost ring observed at 1.3 mm and the shape of spiral features in scattered light observations. The model predicts changes in the disc s dust structure, and star s astrometric parameters, which would allow testing its veracity by monitoring this system over the next 20 yr. © 2021 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.